Rayleigh‐Love Discrepancy Highlights Temporal Changes in Near‐Surface Radial Anisotropy After the 2004 Great Sumatra Earthquake. Issue 12 (10th December 2021) - Yu, W.; Song, T.‐R. A.; Su, J.; Lin, J.‐T.
Abstract: Strong ground motions from large earthquakes are capable of damaging near‐surface sediments and promoting notable reductions in their seismic velocity structures. These velocity reductions can be monitored using either body waves or surface waves from repeatable seismic sources, such as repeating earthquakes (REs) or ambient seismic noise. Here, we compile a decade‐long catalog of REs since the 2004 M w 9.2 Sumatra Earthquake, and monitor the temporal velocity changes from Rayleigh waves ( δV LR ) and Love waves ( δV LQ ). We observe a δV LR of −0.16% and δV LR / δV LQ ratio of ∼6, inconsistent with velocity reductions in isotropic media. To reconcile the observations, we carry out analyses of sensitivity kernels of surface waves in isotropic and vertical transversely isotropic (VTI) media and forward waveform modeling. The modeling reveals that the observed large δV LR / δV LQ ratio can be explained by strong dβ V (−4%) and weak dβ H (−0.615%) reductions and an increase in radial anisotropy in the near surface. These changes are best explained by a 2% increase in crack density of aligned horizontal cracks in overpressured sediments near the compressive subduction zone forearc. Temporal variations of δV LR / δV LQ ratios and radial anisotropy after consecutive great earthquakes are consistent with laboratory experiments under cyclic loading and unloading. Plain Language Summary: This study detects temporal changes in the wave speeds of long‐period Rayleigh and Love waves after the 2004 Great Sumatra Earthquake, which were measured from repeating earthquakes. Seismic observations reveal that the Rayleigh‐wave speed reduction is more than that of Love waves by a factor of 6. Love waves are much more sensitive to the S ‐wave speed of the shallow crust than Rayleigh waves in isotropic media (i.e., the S ‐wave speed is the same in all directions). One would therefore anticipate considerable Love‐wave speed reduction if the S ‐wave speed reduction results from the near surface after great earthquakes. However, the observations indicate the opposite. The result of waveform modeling suggests that these unexpected observations can be suitably explained by an increase in radial anisotropy as a result of increasing fluid‐filled horizontal cracks after great earthquakes. Key Points: We define "Rayleigh‐Love discrepancy" as a stronger velocity reduction of Rayleigh wave than that of Love wave after the Sumatra Earthquake Rayleigh‐Love discrepancy is inconsistent with a velocity change in isotropic media, but an increase in radial anisotropy near the surface Time‐varying Rayleigh‐Love discrepancy reflects changes in fluid‐filled horizontal cracks under cyclic loading by successive earthquakes